Socio-Economic Development and India’s Foreign Trade - JOSHI, DR. VINAY (The journal of contemporary issues in business and government, 2021)
It is evident that exports and imports of India in US dollars have steadily increased in the last 28 years, according to current research. Nevertheless, from year to year, the rate of growth has fluctuated many times negatively. The balance of trade was largely negative. The Research Review discusses the several reasons for the trade movements, the three main reasons why India is compliant with and the trade barriers and globalization;Rupee depreciation against the US dollar, inflammation import bills as well as rising exports. The US sub-prime debt crisis, Europe's debt crisis, is global. For many years, Japan has been in the liquidity trap and a persistent contraction during the UAE and our trading partners. While the miracle countries of Southeast Asia have achieved their objectives by adopting the external orientation model, several countries, especially in India, will have to decide between the "internal" approach to economic development and "outward orientation."